The impact of chorionicity and the type of twin growth on the early neonatal outcome in twin pregnancies - 20 years of experience from one tertiary perinatal center - Wojciech Homola; Jerzy Florjański; Barbara Królak-Olejnik; Tomasz Fuchs; Monika Lachowska; Wiktor Bek (Elsevier, 2019)
Objective: Twin pregnancies are associated with higher neonatal mortality and morbidity. Growth discordance and monochorionicity are among the factors that worsen the course of pregnancy. The study aimed to assess neonatal conditions and mortality in relation to growth type and chorionicity. Materials and methods: Data from 820 pregnant women with twin pregnancies and their 1640 newborns were analyzed. The Apgar score and umbilical artery blood pH, as well as the rate of complications, were compared between dichorionic diamniotic (DCDA) and monochorionic diamniotic (MCDA) twins with symmetric and discordant growth. The Student's t-test and the Pearson chi-square test were used for comparisons. Results: There were 576 (70.2%) DCDA pregnancies, including 421 (73.1%) with symmetric growth and 155 (26.9%) with discordant growth, and 244 (29.8%) MCDA pregnancies, including 110 (45.1%) with symmetric growth and 134 (54.9%) with discordant growth. A significantly greater percentage of twins with discordant growth occurred in women older than 34 years than in those that were younger. An Apgar score of ≤7 was significantly more common among MCDA discordant twins, while an arterial umbilical blood pH of <7.2 was more common among MCDA twins with symmetric growth. Early neonatal deaths (n = 29; 1.8%), respiratory disorders, and a birth weight of <1500 g were significantly more common in MCDA twins than in DCDA twins. Conclusion: MCDA twins with growth discordance are burdened with a higher risk of neonatal morbidity and mortality than symmetric DCDA twins. Chorionicity and growth discordancy are important determinants of the outcome of twin pregnancy. Keywords: Dichorionic diamniotic twins, Growth discordancy, Monochorionic diamniotic twins, Neonatal outcome, Twin growth type